Risser patient satisfaction scale: A validation study in Greek cancer patients - Adamakidou, Theodoula; Charalambous, Andreas (My University, 2012)
Background: The current healthcare climate is characterized by a constant battle for the provision of quality care with limited resources and with patient satisfaction receiving increased attention, there is a need for reliable and valid assessment measures. This study describes the adaptation, testing and validation of the Risser Patient satisfaction Scale in an oncology care setting in Greece. The rationale for this study lies in the scarcity of such measures in the Greek language.Methods: This is a test retest validation study in Greece. Data were collected from 298 hospitalized cancer patients. The validation methodology included the assessment of the item internal consistency, using the Cronbach alpha coefficient. The test-retest reliability was tested by the Kappa correlation coefficient.Results: The scale demonstrated very good psychometric properties. The internal consistency of the instrument was good, Cronbach's alpha was found to be 0.78 (p<0.001) and Kappa coefficient for reproducibility was found to be K=0.89 (95% CI: 0.83-0.91 p<0.0001).Conclusion: The findings demonstrated strong agreement of the scale, suggesting that the Greek version offers substantial reliability. This study provides a valid and reliable tool to assess patient satisfaction in oncology settings. Means to monitor patient satisfaction, a key aspect of the policy agenda for quality care remain important for nurse leaders to develop better care in oncology settings.
Keywords: Cancer patients; Cancer settings; Nursing care; Patient satisfaction; Risser patient satisfaction scale; Validation